Front Cover: 2, 6‐Bis(diazaboryl)pyridine – A Ligand with Hemilabile Donor and Lewis Acid Functionalities (Eur. J. Inorg. Chem. 4/2020). Issue 4 (22nd January 2020) - Schröder, Jan; Böttcher, Tobias
Abstract : The Front Cover shows a version of the video game Tetris. In this game, you must assemble tiles. But not all tiles fit well together. This is like the chemistry presented in this work. Our pyridine ligand (dab2 py) forms adducts with some Lewis acids, but with others it doesn't. For example, dab2 py does not form an adduct with GaCl3 at room temperature. When another main group chloride, GeCl2 in this work, is added to this mixture, the strong Lewis acid GaCl3 abstracts one chloride to form [GaCl4 ] –, and the generated cation is then trapped by coordination of dab2 py to give [(dab2 py)GeCl] + . This is just like Tetris, where you need another tile to complete a row. More information can be found in the Full Paper by J. Schröder and T. Böttcher . For more on the story behind the cover research, see the Cover Profile.